Dilip Hiro, The Longest August: The Unflinching Rivalry between India and Pakistan - Riaz A. Khokhar (CISS Insight Journal, 2018)
“The Indian fixation on cross-border terrorism paralleled Pakistan’s insistence on treating Kashmir as the core problem…India…missed the logical point that terrorism stemmed from…the Kashmir dispute...the cause had to precede the result”, writes Dilip Hiro, the author. The book ‘The Longest August: The Unflinching Rivalry between India and Pakistan” is divided into 20 chapters, encompassing Hindu-Muslim/Indo-Pak rivalry since the British rule/Partition to date. The author’s perspective more often than not supports India’s stance on Indo-Pak bilateral issues such as terrorism and ‘Kashmir insurgency’. His repeated comparison of political systems of India and Pakistan in many ways reflects his preference for Indian political system. The book’s title, the Longest August, stems from the communal bloodbath in August 1947 and the ensuing Indo-Pak rivalry, including three wars, possibility of nuclear Armageddon, terrorist activities and fomenting rebellion in the rival state.